Homemade robots : 10 simple bots to build with stuff around the house - Sarafan, Randy (No Starch Press, 2021)
"A beginner-friendly collection of bot projects that can be built with common items found around the house. Begins with introductory chapters on motors, electronics, and soldering techniques before moving on to the projects, which include step-by-step instructions, photographs, and tips"--